The role of lutein-rich purple sweet potato leaf extract on the amelioration of diabetic retinopathy in streptozotocin-induced Sprague–Dawley rats - Hisamuddin, Ahmad Safiyyu'd-din Bin; Naomi, Ruth; Manan, Khairul Aiman Bin; Bahari, Hasnah; Othman, Fezah; Embong, Hashim; Ismail, Amin; Ahmed, Qamar Uddin; Jumidil, Siti Hadizah; Hussain, Mohd Khairi; Zakaria, Zainul Amiruddin (Frontiers in Pharmacology, 2023)
The objective of this study is to access the effect of purple sweet potato leaves (PSPL) extract on diabetic retinopathy (DR) of streptozotocin (STZ) induced male Sprague Dawley (SD) rats. In this study, rats were injected intraperitoneally with a single dose of 60 mg/kg of STZ and diabetes was confirmed on day 7. The rats were further divided into a few groups which were then orally administered with one of the following treatments; 25 mg/kg of Gliclazide (D25G), 200 mg/kg of PSPL extract (DT 200), and 400 mg/kg of PSPL extract (DT 400), while normal control (NS) and control group for diabetic (DNS) were given normal saline for 12 weeks. The results show treated group shows a reduction in serum oral glucose tolerance test (OGTT) levels of DT 200, and DT 400, an increase in serum and retinal insulin levels, and restore oxidative stress markers in serum and retina on week 12. PSPL extract exhibited protective ef-fects in maintaining the kidney, liver, retina, and pancreas architecture in 400 mg/kg compared to the 200 mg/kg treated group and D25G, thereby restoring fully transparent lenses in diabetic-induced rats. In conclusion, a dosage of 400 mg/kg dosage of PSPL is the most effective dose for the amelioration of STZ-induced DR pathology in male SD rats.